Further Evidence of an Association between the Presence of Leishmania RNA Virus 1 and the Mucosal Manifestations in Tegumentary Leishmaniasis Patients. - Lilian Motta Cantanhêde; Cipriano Ferreira da Silva Júnior; Marcos Massayuki Ito; Kátia Paula Felipin; Roberto Nicolete; Juan Miguel Villalobos Salcedo; Renato Porrozzi; Elisa Cupolillo; Ricardo de Godoi Mattos Ferreira (Public Library of Science (PLoS), 2015)
Tegumentary Leishmaniasis (TL) is endemic in Latin America, and Brazil contributes approximately 20 thousand cases per year. The pathogenesis of TL, however, is still not fully understood. Clinical manifestations vary from cutaneous leishmaniasis (CL) to more severe outcomes, such as disseminated leishmaniasis (DL), mucosal leishmaniasis (ML) and diffuse cutaneous leishmaniasis (DCL). Many factors have been associated with the severity of the disease and the development of lesions. Recent studies have reported that the presence of Leishmania RNA virus 1 infecting Leishmania (Leishmania RNA virus 1, LRV1) is an important factor associated with the severity of ML in experimental animal models. In the present study, 156 patients who attended Rondonia's Hospital of Tropical Medicine with both leishmaniasis clinical diagnoses (109 CL; 38 ML; 5 CL+ML; 3 DL and 1 DCL) and molecular diagnoses were investigated. The clinical diagnosis were confirmed by PCR by targeting hsp70 and kDNA DNA sequences and the species causing the infection were determined by HSP70 PCR-RFPL. The presence of LVR1 was tested by RT-PCR. Five Leishmania species were detected: 121 (77.6%) samples were positive for Leishmania (Viannia) braziliensis, 18 (11.5%) were positive for Leishmania (V.) guyanensis, 3 (1.8%) for Leishmania (V.) lainsoni, 2 (1.3%) for Leishmania (Leishmania) amazonensis and 2 (1.3%) for Leishmania (V.) shawi. Six (3.9%) samples were positive for Leishmania sp. but the species could not be determined, and 4 (2.6%) samples were suggestive of mixed infection by L. (V.) braziliensis and L. (V.) guyanensis. The virus was detected in L. braziliensis (N = 54), L. guyanensis (N = 5), L. amazonensis (N = 2), L. lainsoni (N = 1) and inconclusive samples (N = 6). Patients presenting with CL+ML, DL and DCL were excluded from further analysis. Association between the presence of the virus and the disease outcome were tested among the remaining 147 patients (CL = 109 and ML = 38). Of them, 71.1% (n = 27) mucosal lesions were positive for LRV1, and 28.9% (n = 11) were negative. In cutaneous lesions, 36.7% (n = 40) were positive and 63.3% (n = 69) were negative for LRV1. The ratio P(ML|LRV1+)/P(ML|LRV1-) was 2.93 (CI95% 1.57...5.46; p<0.001), thus corroborating the hypothesis of the association between LRV1 and the occurrence of mucosal leishmaniasis, as previously described in animal models; it also indicates that LRV1 is not the only factor contributing to the disease outcome.